8. EVALUATION THE EFFICIENCY AND SAFETY OF ALBENDAZOL AND IVERMECTIN ON TOXOCARA INFECTED PATENTS AT THONG NHAT - DONG NAI GENERAL HOSPITAL FROM 2022 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Introductions: Toxocariasis is commonly infected from dogs and causes an inflammatory reaction that damages tissues and related organs where they pass through, leading to the syndrome of moving larvae (ATDC). This disease is more prevalent in our country than the global average.Research objective: To evaluate the effecticiency and safety of Albendazole and Ivermetin in patients with toxocariasis.Research subjects and methods: Retrospective and prospective study of 88 patients diagnosed with Toxocara canis infection at Thong Nhat Dong Nai General Hospital from June 2022 to June 2023. Research on clinical and subclinical characteristics, treatment efficiency and safety of Albendazole and Ivermectin.Results: The average age of patients was 50.5 years old, the most common source of disease was in households with pets and close contact with dogs and/or cats. Common symptoms on the skin and mucous membranes included itchy rashes (81.8%), eyebrows urticaria (55.6%), 35% of patients had a mild increase in the number of eosinophils in peripheral blood), unwanted drug effects appeared in 30.6% of patients, including dizziness and/or headache (17%), ). After 3 months of treatment, the rate of clinical and subclinical symptoms statistically decreased.Conclusion: Characteristics of Toxocariasis cases infected from dogs and cats are commonly composed of symptoms of itching and hives, possibly increased eosinophils in peripheral blood, ELISA test for anti-Toxocara antibodies. spp. IgG positive. The efficiency of Albendazole and Ivermectine in toxocariasis is high and side effects are mild and transient.
Keywords: Toxocaracanis, dog and cat roundworm larvae.